2017
DOI: 10.31223/osf.io/pfb7u
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A general model for the helical structure of geophysical flows in channel bends

Abstract: Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It has previously been suggested that secondary (across-channel) helical flow causing gradual bend migration, is the main control on submarine channel evolution, as is the case for many rivers. There has been considerable debate over whether the sense of submarine secondary circulation is river-like or reversed 25,31,55,56 . Outer-bend erosion causing lateral migration is common in Bute Inlet and can locally reach rates of over 10 m/year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been suggested that secondary (across-channel) helical flow causing gradual bend migration, is the main control on submarine channel evolution, as is the case for many rivers. There has been considerable debate over whether the sense of submarine secondary circulation is river-like or reversed 25,31,55,56 . Outer-bend erosion causing lateral migration is common in Bute Inlet and can locally reach rates of over 10 m/year.…”
Section: Resultsmentioning
confidence: 99%
“…First, it has been proposed that submarine channels evolve in a broadly comparable way to meandering rivers, via gradual outer-bend erosion and inner-bend deposition, and meander bend cut-off 5,23,26 . Bend migration and cut-off is primarily driven by cross-channel (secondary) flow and has long been known to be a dominant control on how rivers evolve [27][28][29][30] , and also occurs in submarine channels 31 . However, submarine channels have been suggested to differ in key regards from rivers 32 .…”
mentioning
confidence: 99%
“…The oblique directions of the flow can either be due to the sharp turn in the canyon axis, which leads to helical flows around meander bends (e.g. Azpiroz‐Zabala et al ., 2017b) or to the shape of the crescentic bedforms that permits flows to travel obliquely on the sides of the canyon. The velocity peaks are coincident with peaks in backscatter in the water column, indicative of peaks in suspended sediment concentration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with these observations, as well as with previous field studies (see Pivato et al, 2018), direct measurements at the study sites highlighted uniform vertical temperature profiles. Hence, we can effectively rule out the chance for the observed secondary flow dynamics to be partially driven by stratification effects (e.g., Azpiroz‐Zabala et al, 2017; Sumner et al, 2014).…”
Section: Methodsmentioning
confidence: 98%